A risk assessment of Pseudomonas aeruginosa in swimming pools : a review - Rice, Scott A. (2013)
Despite routine monitoring and disinfection, treated swimming pools are frequently contaminated with the opportunistic pathogen Pseudomonas aeruginosa, which can represent a significant public health threat. This review was undertaken to identify the current understanding of risk factors associated with pool operation with respect to P. aeruginosa. The ecology and factors that promote growth of P. aeruginosa in the pool environment are complex and dynamic and so we applied a systematic risk assessment approach to integrate existing data, with the aim to improve pool management and safety. Sources of P. aeruginosa, types of infections, dose responses, routes of transmission, as well as the efficacy of current disinfectant treatments were reviewed. This review also highlights the critical knowledge gaps that are required for a more robust, quantitative risk assessment of P. aeruginosa. Quantitative risk management strategies have been successfully applied to drinking water systems and should similarly be amenable to developing a better understanding of the risk posed by P. aeruginosa in swimming pools.